2016
DOI: 10.1002/erv.2459
|View full text |Cite
|
Sign up to set email alerts
|

Does the Interpersonal Model Generalize to Obesity Without Binge Eating?

Abstract: The interpersonal model has been validated for binge eating disorder (BED), but it is not yet known if the model applies to individuals who are obese but who do not binge eat. The goal of this study was to compare the validity of the interpersonal model in those with BED versus those with obesity, and normal weight samples. Data from a sample of 93 treatment-seeking women diagnosed with BED, 186 women who were obese without BED, and 100 controls who were normal weight were examined for indirect effects of inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 46 publications
3
22
2
Order By: Relevance
“…Although there is some evidence that BED is associated with greater psychopathology than their weight-matched counterparts without BED (Ivezaj et al, 2016; Lo Coco et al, 2016), there were no differences between the two groups concerning the specific personality traits (viz., impulsivity, reward sensitivity, and anxiety-proneness) assessed in our study.…”
Section: Discussionmentioning
confidence: 87%
“…Although there is some evidence that BED is associated with greater psychopathology than their weight-matched counterparts without BED (Ivezaj et al, 2016; Lo Coco et al, 2016), there were no differences between the two groups concerning the specific personality traits (viz., impulsivity, reward sensitivity, and anxiety-proneness) assessed in our study.…”
Section: Discussionmentioning
confidence: 87%
“…The findings suggest that overweight women without BED may use similar ways of regulating their affect and experience similar types of interpersonal problems as women with BED. Lo Coco et al () reported that negative affect plays a complex role in the interpersonal functioning and weight of obese women without BED that is not yet fully understood. As suggested by Lo Coco et al (), negative affect may lead to and be a consequence of interpersonal problems, and both of these issues may result in overeating and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Lo Coco et al () reported that negative affect plays a complex role in the interpersonal functioning and weight of obese women without BED that is not yet fully understood. As suggested by Lo Coco et al (), negative affect may lead to and be a consequence of interpersonal problems, and both of these issues may result in overeating and obesity. Our findings suggest that similar to women with BED, overweight women without BED use both hyperactivating and deactivating affect regulation strategies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations